A Comparative Study of Dichotomic Perspectives in the Writings of Charles Dickens and Arundhati Roy: Exploring the Dichotomic Perspectives and Writing Styles of Charles Dickens and Arundhati Roy (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Charles Dickens uses the art of honest imagination and sarcastic unity in ordinary times and words and shows no apathy in dividing social evils in the society and brings people against their anger and makes people aware. Charles Dickens was not only a metaphor but also an orator (character of the deacon). His main concern was the transfer of information, but as an author, he was also interested in making beautiful books. The writing was very successful. He used exaggeration to describe the nature of behavior. He enjoys symbolic, figurative, and often repetitive phrases to emphasize sentences making it easier for him to read and understand his work and to remember his words.Arundhati Roy's writing style consists of synthesized and mixed-use situations that focus on abstract situations and use new writing methods found in the rebellion. She makes good use of 'casting, class, sex n'.